Efficacy of Ethanol Extract of Fructus lycii and Its Constituents Lutein/Zeaxanthin in Protecting Retinal Pigment Epithelium Cells against Oxidative Stress: In Vivo and In Vitro Models of Age-Related Macular Degeneration - Xinrong Xu; Li Hang; Binglin Huang; Yuanhua Wei; Shizhong Zheng; Wei Li (Journal of Ophthalmology)
Age-related macular degeneration (AMD) is a major cause of blindness worldwide. Oxidative stress plays a large role in the pathogenesis of AMD. The present study was to evaluate the effects of Fructus lycii ethanol extract on AMD in mice and to investigate whether combination of lutein and zeaxanthin, two carotenoid pigments in Fructus lycii, could protect human retinal pigment epithelial ARPE-19 cells treated with hydrogen peroxide (H2O2) in vitro. We found that severe sediment beneath retinal pigment epithelium and thickened Bruch membrane occurred in AMD mice. However, Fructus lycii ethanol extract improved the histopathologic changes and decreased the thickness of Bruch membrane. Furthermore, the gene and protein expression of cathepsin B and cystatin C was upregulated in AMD mice but was eliminated by Fructus lycii ethanol extract. Investigations in vitro showed that ARPE-19 cell proliferation was suppressed by H2O2. However, lutein/zeaxanthin not only stimulated cell proliferation but also abrogated the enhanced expression of MMP-2 and TIMP-1 in H2O2-treated ARPE-19 cells. These data collectively suggested that Fructus lycii ethanol extract and its active components lutein/zeaxanthin had protective effects on AMD in vivo and in vitro, providing novel insights into the beneficial role of Fructus lycii for AMD therapy.